Effect of adhesive quantity on selected physico-mechanical properties of bamboo glulam - Yekin Ogunsanwo, Olukayode; Omobolaji Adenaiya, Adewunmi; Aderonke Adedeji, Christianah (Maderas. Ciencia y Tecnología, 2019)
This study was aimed at determining the optimal glue quantity for bamboo lamination. Bamboo laminated boards were produced using glue applied at three different rates: 150 g/m2, 200 g/m2 and 250 g/m2. The boards produced were evaluated for their physical (density, longitudinal, tangential, radial and volumetric shrinkage) and mechanical (impact bending strength, modulus of elasticity, modulus of rupture and maximum compressive strength parallel to grain properties. It was discovered that the boards were uniform in their investigated physical properties but the glue quantity significantly influenced both the impact bending strength and modulus of rupture of the boards. Based on the results, it was observed that the boards produced with glue applied at the rate of 200 g/m2 met all the technical specifications on the basis of the investigated physical and mechanical properties, hence, concluded to be the optimal glue quantity for bamboo lamination.